Can sharing auditors with customers improve suppliers digital transformation? - Liu, Xiaohui; Chen, Yan (Frontiers in Psychology, 2024)
Promoting enterprises digital transformation is the fundamental path to implementing the digital China strategy and realizing high-quality development. Taking China's A-share listed companies from 2007 to 2021 as a research sample, this paper examines the impact of sharing auditors with customers on the digital transformation of suppliers. The results show that sharing auditors with customers can promote suppliers' digital transformation, and this promotion effect is stronger among suppliers with weaker bargaining power, lower media attention, and higher auditor industry expertise. In terms of the mechanism of action, sharing auditors with customers can help strengthen the supervision of the supplier, alleviate suppliers' financing constraints, and thus facilitate their digital transformation. Further research finds that when suppliers share auditors with their customers, suppliers' digital transformation helps to promote their innovation level. The research conclusion provides effective empirical evidence for alleviating the dilemma of digital transformation of enterprises.